Comparison of enzymatic and bisulfite-based methods for sequencing-based cell-free DNA methylation profiling - Ezegbogu, Mark; Stockwell, Peter Averill; Reid, Glen; Brockway, Ben; Kumar, Rajiv; Rodger, Euan; Chatterjee, Aniruddha (Frontiers in Epigenetics and Epigenomics, 2026)
Epigenetic analysis, especially DNA methylation profiling of plasma cell-free DNA (cfDNA), has recently emerged as a promising clinical tool. Choosing the right analytical method is crucial for working with limited cfDNA, ensuring cost-effectiveness, and supporting clinical translation. While bisulfite-based methods have long been the standard for methylation analysis, enzymatic conversion is a potential alternative. However, their comparative performance for cfDNA remains unclear. In this study, we compared enzymatic (EM-Seq) and bisulfite-based (cfRRBS and cfMethyl-seq) methods. EM-Seq showed higher mapping efficiency, broader genomic coverage, and captured more CpGs at low coverage thresholds, while the bisulfite methods had higher conversion rates, lower costs, and better coverage of functional regions like promoters and exons. The bisulfite-based methods also demonstrated superior reproducibility. Overall, cfRRBS offered the best balance of cost, accuracy, and reproducibility. Our findings fill a key gap in cancer epigenetics, outline the strengths and limitations of each method, and provide a practical guide for selecting cfDNA methylation profiling methods in liquid biopsy applications.